Contribuição ao estudo das Bacillariophyceae (Diatomáceas) de Caiobá, Estado do Paraná, Brasil - Moreira, Ita Moema Valente; Filho, Hermes Moreira (Acta Biológica Paranaense, 1981)
Contribuição ao estudo das Bacillariophyceae (Diatomáceas) de Caiobá, Estado do Paraná, Brasil